Integrated Management of Major Coconut Pests Using Pheromone Lures - Bhanu, K. R. M.; Jayanth, K. P.; Mathew, M. Thomas; Prabhakara, M. S. (International Coconut Community, 2012)
Red palm weevil Rhynchophorus ferrugineus Olivier (Coleoptera: Curculionidae; Rhinoceros beetle Oryctes rhinoceros Linn. (Coleoptera: Scarabidae) and Black headed caterpillar Opisina arenosella Walker (Lepidoptera: Oecophoridae) are the three among major insect pests of coconut in India. Grubs of Red palm weevil (RPW) enter and complete their life cycle within the stem, killing the tree, adults of Rhinoceros beetle (RB) feed on the growing point of the tree and cause yield loss and the larvae of black headed caterpillar scrape and feed on the green part of the coconut leaflets leading to burnt symptoms of the fronds, death of young trees and yield loss. Aggregation pheromones of RPW and RB are used for monitoring and mass trapping of RPW and RB to manage the pest under economic threshold level. During 2006-07 large scale field trials for RPW and RB were carried out in four different states in India by PCI under a partially funded Coconut Development Board (CDB) project using indigenously synthesized pheromone lures. It was demonstrated that the pheromone lures predominantly attracted virgin and gravid females of RPW and RB. Female sex pheromone of black headed caterpillar Opisina arenosella was also identified and developed in India by PCI, under a project partially funded by CDB; dispensers, dosage and traps were standardized under field conditions and further trials were also conducted in India. It was also established that pheromone lures can be used as a monitoring and a surveillance tool for understanding the pest status before the release parasitoids and natural enemies.